Correlation Abnormal Ankle-Brachial Index and Multivessel Coronary Artery Disease in Acute Coronary Syndrome Patients - Idar Mappangara; Magma Purnawan Putra; Khalid Saleh (The Indonesian Biomedical Journal, 2017)
BACKGROUND: Many studies showed the association between peripheral artery disease (PAD) and coronary artery disease (CAD). The anklebrachial index (ABI) was a simple, noninvasive, and not expensive test that showed high sensitivity and specificity in the diagnosis of PAD. Previous studies showed PAD correlation with the number of coronary artery lesions and higher complexity of the lesions. These correlations might contribute to worse cardiovascular outcomes, especially acute coronary syndrome (ACS) cases. Aim of this study is to evaluate the correlation abnormal ABI with the risk of ACS patients to have multivessel coronary artery lesions.METHODS: This was a retrospective analytical casec ontrol study. The data were taken from Dr. Wahidin Sudirohusodo Hospital medical records from November 2015 to February 2016. The inclusion criteria were (>18 years old) patients with ACS who had underwent ABI examination and coronary angiography.RESULTS: The prevalence of patients with ST-elevation myocardial infarction (STEMI) was lower than non-ST elevation ACS (NSTE-ACS). The prevalence of patients with abnormal ABI was 43.3% and patients with multivessel CAD was 65%. Male patients dominated the ACS population with 73.3%, about half of patients were smoking, and 86.7% had dyslipidemia. Patients with abnormal ABI and multivessel disease had greater number than patients with normal ABI (p=0.025). Analysis with binary logistic regression model showed abnormal ABI (odd ratio [OR] 4.83; p=0.021) and male sex (OR 19.35; p=0.010) were associated with greater risk of multivessel CAD.CONCLUSION: An abnormal ABI is associated with greater risk of multivessel CAD in ACS patients.KEYWORDS: ankle-brachial index, multivessel, coronary, acute coronary syndrome